2007
DOI: 10.2514/1.30500
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Critical Fuel Configurations Using Robust Flutter Analysis

Abstract: An approach to assess critical fuel configurations using robust flutter analysis is presented. A realistic aircraft model is considered to demonstrate how an available finite element model can be adapted to easily apply robust flutter analysis with respect to structural variations such as fuel-level variations. The study shows that standard analysis tools can be used to efficiently generate the system data that are required to perform robust flutter analysis. The -k method is used to compute the worst-case flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Only aerodynamic uncertainty is treated in this study although, it is also possible to consider uncertainties in the structural model [15,16]. A standard panel-type aerodynamic model is used in this study; see Sec.…”
Section: Aerodynamic Uncertainty Modelingmentioning
confidence: 99%
“…Only aerodynamic uncertainty is treated in this study although, it is also possible to consider uncertainties in the structural model [15,16]. A standard panel-type aerodynamic model is used in this study; see Sec.…”
Section: Aerodynamic Uncertainty Modelingmentioning
confidence: 99%
“…Basically, using for robust flutter analysis is a sophisticated search in the parameter space for the most critical perturbation. Unfortunately, the most critical perturbation as such is not a result of the upper-bound computation, but it can be estimated by other means [9,19]. In this work, the solver in MATLAB [20] was used for the analysis, using the default settings.…”
Section: Equivalent Feedback Formmentioning
confidence: 99%
“…The -k formulation also opened up new possibilities to model aerodynamic uncertainty, which is of primary importance in aeroelastic applications. Some additional developments in this direction can be found in [7][8][9][10].…”
mentioning
confidence: 99%
“…In the past few years, many scholars have done some research on the influence of wing fuel mass variations on the aeroelasticity. Heinze (Heinze, 2007) used μ-κ method to assess the influence of wing fuel variations on the flutter boundary in subsonic regime. It was shown that the variation of the structural mode shapes due to fuel mass variation play a significant role in flutter speed of the aircraft.…”
Section: Introductionmentioning
confidence: 99%